Approaches towards tick and tick-borne diseases control. - Domingos, Ana Isabel Amaro Gonçalves (2013)
Ticks are obligate haematophagous ectoparasites of wild and domestic animals as well as humans, considered to be second worldwide to mosquitoes as vectors of human diseases. Tick-borne diseases are responsible worldwide for great economic losses in terms of mortality and morbidity of livestock animals. This review concerns to the different tick and tick-parasites control methods having a major focus on vaccines. Control of tick infestations has been mainly based on the use of acaricides, a control measure with serious drawbacks, as responsible for the contamination of milk and meat products, as a selective factor for acaricide-resistant ticks and as an environmental contaminant. Research on alternatives to the use of acaricides is strongly represented by tick vaccines considered a more cost-effective and environmentally safe strategy. Vaccines based on the Bm86 tick antigen were used in the fi rst commercially available cattle tick vaccines and showed good results in reducing tick numbers, affecting weight and reproductive performance of female ticks which resulted in reduction of cattle tick populations over time and consequently lower reduction of the pathogen agents they carry.